2022
DOI: 10.1007/s43393-022-00081-z
|View full text |Cite
|
Sign up to set email alerts
|

Production, purification and activity evaluation of three novel antioxidant peptides obtained from grass carp (Ctenopharyngodon idella) scale waste by microbial protease BaApr1 hydrolysis

Abstract: In this study, an alkaline protease BaApr1 from the Bacillus altitudinis W3 was chosen to hydrolysis grass carp (Ctenopharyngodon idella) scales. The hydrolysate of alkaline protease BaApr1 exhibited the best antioxidant activity compared to other protease hydrolysates. The optimal hydrolysis conditions for BaApr1 were an enzyme dosage of 1250 U/g, a hydrolysis time of 7 h, a pH of 9.5 and a temperature of 50 °C. Three novel peptides were purified using ultrafiltration, anion exchange chromatography, gel filtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…10 Many studies have demonstrated the overlooked potential value of discarded grass carp fish scales and their important biomedical potential. 11,12 In our previous studies, we successfully fabricated a biomaterial with a lamellar structure utilizing grass carp fish scales and demonstrated its capacity for bone regeneration. 13,14 This grass carp fish-scalebased membrane effectively facilitated the attachment, proliferation, and osteogenic differentiation of bone marrow mesenchymal stem cells 13 and exhibited remarkable osteogenic potential in rat craniofacial bone defect models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Many studies have demonstrated the overlooked potential value of discarded grass carp fish scales and their important biomedical potential. 11,12 In our previous studies, we successfully fabricated a biomaterial with a lamellar structure utilizing grass carp fish scales and demonstrated its capacity for bone regeneration. 13,14 This grass carp fish-scalebased membrane effectively facilitated the attachment, proliferation, and osteogenic differentiation of bone marrow mesenchymal stem cells 13 and exhibited remarkable osteogenic potential in rat craniofacial bone defect models.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, fish-derived collagen has gained attention as a substitute for mammalian-derived collagen because of its low immunogenicity and excellent biocompatibility. , The grass carp (Ctenopharyngodon idella) is the most widely produced aquaculture species worldwide, with a total of 5.8 million tons harvested in 2020 . Many studies have demonstrated the overlooked potential value of discarded grass carp fish scales and their important biomedical potential. , In our previous studies, we successfully fabricated a biomaterial with a lamellar structure utilizing grass carp fish scales and demonstrated its capacity for bone regeneration. , This grass carp fish-scale-based membrane effectively facilitated the attachment, proliferation, and osteogenic differentiation of bone marrow mesenchymal stem cells and exhibited remarkable osteogenic potential in rat craniofacial bone defect models . Collagen is the most abundant component of the osteogenic extracellular matrix (ECM) and plays a crucial role in the process of in vivo biomineralization. , Although grass carp fish scales are rich in type I collagen, , their application in biomedicine or tissue engineering has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%